Penetapan Technical Assistance Service Fee dan Management Fee sebagai Proceeds dalam Audit Kepabeanan - Azmi, Hilmi Aulia; Susanto , Dwi Setiawan (Politeknik Ganesha Medan, 2024)
The determination of costs such as the Technical Assistance Service Fee and Management Fee as proceeds is not approved by the auditee in the audit process. The auditee believes that these costs are payments for services provided by overseas entities and are not related to proceeds. After the determination was made by the customs audit team, PT ABC and PT XYZ submitted an appeal to the Tax Court and the panel of judges issued a different decision regarding the determination. The regulations regarding proceeds themselves are still limited, only regulating definitions and not yet regulating the criteria and limitations in detail. The research questions that will be raised in this study are why the TAS Fee and Management Fee payments are designated as proceeds and why there are differences in decisions from the Tax Court Panel of Judges. This research was conducted using a case study strategy with a qualitative approach. The data used is secondary data in the form of Tax Court decisions and primary data in the form of interviews. The data analysis methods used are content analysis, thematic analysis, and constant comparative analyses The results of the research show that there is a similar pattern and consistency in determining costs as proceeds by the audit team for two different auditees. However, at the Tax Court level, there are differences in the decision of the Panel of Judges, namely that the Panel determines the team's analysis that a fee can be designated as proceeds if it meets the definition in the regulations, and another decision determines that a service fee cannot be determined other than what is agreed in the agreement.